The Endoplasmic Reticulum Chaperone GRP170: From Immunobiology to Cancer Therapeutics - Wang, Hongxia; Pezeshki, Abdul Mohammad; Yu, Xiaofei; Guo, Chunqing; Subjeck, John R.; Wang, Xiang-Yang (Frontiers in Oncology, 2015)
Glucose-regulated protein 170 (GRP170) is the largest member of GRP family that resides in the endoplasmic reticulum (ER). As a component of the ER chaperone network, GRP170 assists in protein folding, assembly, and transportation of secretory or transmembrane proteins. The well documented cytoprotective activity of intracellular GRP170 due to its intrinsic chaperoning property has been shown to provide a survival benefit in cancer cells during tumor progression or metastasis. Accumulating evidence shows that extracellular GRP170 displays a superior capacity in delivering tumor antigens to specialized antigen-presenting cells for cross-presentation, resulting in generation of an antitumor immune response dependent on cytotoxic CD8+ T cells. This unique feature of GRP170 provides a molecular basis for using GRP170 as an immunostimulatory adjuvant to develop a recombinant vaccine for therapeutic immunization against cancers. This review summarizes the latest findings in understanding the biological effects of GRP170 on cell functions and tumor progression. The immunomodulating activities of GRP170 during interactions with the innate and adaptive arms of the immune system as well as its therapeutic applications in cancer immunotherapy will be discussed.